Assessment of Armed Forces Radio Programming in the Civil-Military Relationship in FCT - Oladimeji Saheed Olanrewaju; Gana Hope; Musa Mathias; Anthony Ogande (International Journal of Education, Culture, and Society, 2026)
Civil–military relations remain a critical dimension of national cohesion and public trust, and broadcast media increasingly serve as a strategic platform for fostering mutual understanding between civilians and military institutions. This study assessed the impact of Armed Forces Radio programming on civil–military relations in the Federal Capital Territory. Guided by Agenda Setting Theory, the study employed a survey research design using a questionnaire to elicit data from respondents. From a population of 1,693,400, a sample of 400 participants was selected for the study. The findings showed that 79% of members of the public within the AMAC community had regular access to Armed Forces Radio and were allowed to participate in programmes promoting civil–military relations. The study further revealed that Armed Forces Radio programming has a significant positive impact on fostering understanding and collaboration between civilians and the military in real-life contexts, although some audience members remained skeptical about the military’s sincerity in sustaining peace and cordial relations with civilians. These findings indicate that the military has made deliberate efforts through broadcasting to create a platform for strengthening civil–military relations. The study therefore underscores the importance of expanding signal coverage to rural areas and sustaining audience-centered programming to consolidate positive public perception and enhance participatory communication in support of stronger civil–military engagement.